Reform of corporate criminal liability arrangements in Indonesia and types of sanctions that can be implemented - Sembiring, Rya Elita Br; Pujiyono, Pujiyono (Legality : Jurnal Ilmiah Hukum, 2020)
Individuals who commit criminal acts will receive criminal sanctions for them. However, criminal sanctions for corporations that commit criminal acts are not regulated in the Criminal Code. This research uses normative legal research methods. This study aims to examine the criminal liability arrangements by corporations as well as what sanctions can be applied. In Indonesia, criminal liability by corporations has been regulated in several statutory regulations that are outside the Criminal Code. Sanctions that can be applied to corporations include basic crimes such as criminal fines, additional crimes, and corporate confiscation.